Nanoparticle Preparation Using the Single Microemulsions Scheme - Husein, Maen M.; Nassar, Nashaat N. (Current Nanoscience, 2008)
Nanoparticles serve the need for advanced materials with specific chemical, physical, and electronic properties. These properties can be attained by manipulating the particle size. Consequently, size control has been recognized as a key factor for selecting a nanoparticle preparation technique. (w/o) Microemulsions, or reverse micelles, have been successfully used to prepare wide variety of nanoparticles with controlled sizes. Studies showed that adjusting microemulsion and/or operation variables provides a key to controlling nanoparticle size and polydispersity. The effect of a given variable, however, relies heavily on the reactant addition scheme. The mixing of two microemulsions scheme has been widely used in the literature, and the effect of microemulsion and operation variables on intermicellar nucleation and growth was detailed. The single microemulsions reactant addition scheme, on the other hand, enables intramicellar nucleation and growth, and therefore, may lead to a different response. Moreover, studies on nanoparticle preparation using the single microemulsions scheme involved more of reactive surfactants and introduced the concept nanoparticle uptake, which pertains to the maximum colloidal concentration of nanoparticles that can be stabilized in a microemulsion system. This review looks into the mechanisms controlling nanoparticle formation and compares literature trends reported for the effect of microemulsion and operation variables on the nanoparticle size and polydispersity for the single microemulsions reactant addition scheme. Moreover, it sheds some light on nanoparticle uptake and its significance.
Keywords: Nanoparticle